The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1089/tmj.2018.0328
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Screening Units for the Early Detection of Breast Cancer and Cardiovascular Disease: A Pilot Telemedicine Study in Southern Italy

Abstract: Introduction: Telemedicine is the use of Information and Communication Technologies (ICT) to improve patient outcomes by increasing access to care, medical information and services. The aim of this pilot study was to evaluate and support the implementation of screening and early detection programs in the prevention of breast cancer and cardiovascular diseases with the establishment of a remote diagnosis through the use of ICT in mobile units. Materials and Methods: A total of 430 individuals were recruited in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The use of telemedicine in BCa screening programs have been effective in the discovery of early lesions [43]. Marino described a pilot telemedicine study involving the use of mobile units in a BCa screening program and found that 3.1% of the cases had suspicious malignant lesions, 40.8% were negative to lesions and 34.9% of cases were positive to benign lesions [44]. Chung et al described the potential application of telemammography which could increase health care provision and access for BCa patients [45] as it facilitates communication between primary physicians and specialist, and ultimately improved patient outcomes [46].…”
Section: Telehealth Covid-19 and Breast Cancer Screeningmentioning
confidence: 99%
“…The use of telemedicine in BCa screening programs have been effective in the discovery of early lesions [43]. Marino described a pilot telemedicine study involving the use of mobile units in a BCa screening program and found that 3.1% of the cases had suspicious malignant lesions, 40.8% were negative to lesions and 34.9% of cases were positive to benign lesions [44]. Chung et al described the potential application of telemammography which could increase health care provision and access for BCa patients [45] as it facilitates communication between primary physicians and specialist, and ultimately improved patient outcomes [46].…”
Section: Telehealth Covid-19 and Breast Cancer Screeningmentioning
confidence: 99%
“…The use of telemedicine in BCa screening programs have been effective in the discovery of early lesions [43]. Marino described a pilot telemedicine study involving the use of mobile units in a BCa screening program and found that 3.1% of the cases had suspicious malignant lesions, 40.8% were negative to lesions and 34.9% of cases were positive to benign lesions [44]. Chung et al described the potential application of tele-mammography which could increase health care provision and access for BCa patients [45] as it facilitates communication between primary physicians and specialist, and ultimately improved patient outcomes [46].…”
Section: Telehealth Covid-19 and Breast Cancer Screeningmentioning
confidence: 99%
“…The proposed model was built in an environment for domiciliary rehabilitation based on lung incentive gamified devices integrated into the e-Healthcare system. Marino et al (2019), sought to evaluate the implementation of screening programs and early detection in the prevention of breast cancer and cardiovascular diseases with the establishment of a remote diagnosis through Telemedicine in a sample composed of 321 women submitted to breast cancer screening and 109 individuals undergoing cardiovascular screening, such study was developed in southern Italy. For the sample studied, the authors concluded that the use of telemedicine significantly reduces the costs of breast cancer tracking and major cardiovascular diseases.…”
Section: Previous Studies About E-healthcarementioning
confidence: 99%